HEALTH RELATED QUALITY OF LIFE OUTCOME IN PATIENTS WITH CHRONIC HEPATITIS C, REVIEW CONCEPTUAL MODELS: Life Science - Medical - POURGHOLAM AMIJI, NIMA; MOAYED ALAVIAN, SEYED (International Journal of Life Science and Pharma Research, 2017)
Chronic hepatitis C (CHC) and its treatment are associated with different patient-reported symptoms and impacts. This literature review intend to identify concepts raised by CHC patients related to symptoms, treatment effects, and evaluated integration of these concepts within patient-reported outcome (PRO) measures. Hence Health related quality of life (HRQOL) is increasingly used as an outcome in clinical trials, effectiveness research, and research on quality of care. Factors that have facilitated this increased usage include the accumulating evidence that measures of HRQOL are valid and reliable. The publication of several large clinical trials showing that these outcome measures are responsive to important clinical changes. In this article, we reviewed some conceptual multi-dimensional models of HCV quality of life patients. The content dimensions were fitted to the domains and treatment dimensions. This review identified several gaps in the literature relating to assessment of symptoms and outcomes reported as important by CHC patients. A lot more research is needed to make certain that CHC clinical trials evaluate concepts that are important to patients and include measures that have evidence supporting content validity and reliability.